2022
DOI: 10.1177/21582440221082146
|View full text |Cite
|
Sign up to set email alerts
|

Service Innovation, Marketing Innovation and Customer Satisfaction: Moderating Role of Competitive Intensity

Abstract: Based on dynamic capability and contingency theory, authors examined the direct connection between Service innovation, Marketing innovation and Customer satisfaction, and the interacting mechanism of competitive intensity. The research model and hypotheses were developed from extant studies. Respondents from 300 microfinance banks participated in the survey. Analyses in Smart PLS software showed that Service innovation positively and significantly affects Customer satisfaction. Marketing innovation promotes cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 81 publications
1
2
0
Order By: Relevance
“…However, understanding that customer demands are constantly evolving in the face of changing world conditions is essential. The study partly supports the literature, paralleling findings by Chen et al (2015), Bellingkrodt and Wallenburg (2015), Nwachukwu and Vu (2022), Cabral and Marques (2020), indicating that the innovation activities of the airline company partially affect the perceived service quality by customers. Potential differences in the interpretation of survey questions across various sectors discussed in the existing literature contribute to this partial support.…”
Section: Conclusion and Recommendationssupporting
confidence: 83%
“…However, understanding that customer demands are constantly evolving in the face of changing world conditions is essential. The study partly supports the literature, paralleling findings by Chen et al (2015), Bellingkrodt and Wallenburg (2015), Nwachukwu and Vu (2022), Cabral and Marques (2020), indicating that the innovation activities of the airline company partially affect the perceived service quality by customers. Potential differences in the interpretation of survey questions across various sectors discussed in the existing literature contribute to this partial support.…”
Section: Conclusion and Recommendationssupporting
confidence: 83%
“…Similarly, several studies found that MI is critical for the marketing performance (Breesama et al, 2019;Lee et al, 2016) and it has also a significant effect on innovation performance (Medase & Barasa, 2019). MI also has a positive significant effect on the performance of companies (Peng et al, 2021), as well as customer satisfaction (Nwachukwu & Vu, 2022). On the other hand, studies also found that MI has no effect on the firm performance as reported in the study of Sayangbatti and Riyadi (2021).…”
Section: Marketing Innovation and Smebpmentioning
confidence: 81%
“…Examples of innovative marketing ventures include immersive experiential campaigns, augmented reality advertisements, personalised and data-driven content strategies, influencer collaborations and interactive social media campaigns. The essence of such ventures lies in their ability to captivate consumer attention, create memorable brand experiences, and adapt to the ever-evolving landscape of consumer preferences and technological advancements (Chijioke, Vu, 2022;Chummee, 2022).…”
Section: Discussionmentioning
confidence: 99%